Programmable NIR Responsive Nanocomposite Enables Noninvasive Intratympanic Delivery of Dexamethasone to Reverse Cisplatin Induced Hearing Loss - Mustaf, Rawand A.; Wang, Jiali; Xun, Mengzhao; Rosenholm, Jessica M.; Wang, Wuqing; Shu, Yilai; Zhang, Hongbo (Wiley, 2025)
Local intratympanic drug delivery to the inner ear possesses significant otological clinical promise as cisplatin-induced hearing loss (CIHL) therapy, inducing significantly less side effects than systemic drug delivery. However, the multiple detoured barriers, round window membrane (RWM) and poorly controlled drug release hinder successful non-invasive drug delivery through intratympanic administration (IT). Here, a novel near-infrared (NIR) responsive nanocomposite functionalized with saponin, denoted gold nanorod@dexamethasone-mesoporous silica-saponin (AuNR@DEX-MS-saponin, NPs/DEX), is developed to enhance RWM permeation and to control the drug release spatiotemporally. First, the physiochemical properties and release profile of the synthesized nanocomposites are assessed, after which the biocompatibility of the nanocomposites and oto-protection against CIHL are shown in vitro and in vivo. The findings demonstrated that DEX is delivered to the inner ear with high efficiency through IT, due to the permeation enhancement effect of the nanocomposite. Moreover, the nanocomposite with low dose of DEX is highly effective in recovering CIHL, attenuating hair cell loss, and alleviating synaptic ribbon damage. These findings provide insight into NIR-responsive local delivery for inner ear illnesses.